If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3-4)+4*3*-3=0
We simplify the equation to the form, which is simple to understand
(3-4)+4*3*-3=0
Simplifying:
(3-4)+12*-3=0
Simplifying:
(3-4)+36=0
Simplifying terms in parentheses
(-1)+36=0
Remove unnecessary parentheses
-1+36=0
We move all terms containing to the left and all other terms to the right.
0=0+1-36
We simplify left and right side of the equation.
0=-35
0=-35
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= | | 4/3p=16 | | h(t)=5t^2-30t+45 | | 3/2n=15 | | 2(-3)+16-(3+4)= | | B=900(1+.02) | | d/5+4=9 | | 24-6x=24 | | 20(t)=5t^2-30t+45 | | 5(X+3)-3X=55 | | -5(t-5)+7=6t-3 | | 3x+97=7x+37 | | 3x-29=6x-89 | | 6(4+y)=5(y-2) | | 3x^2-x=7 | | 6x+163=8x+187 |